Impact of soil physical properties on the driving performance of a tracked tractor on paddy soils in the plastic state - CAO Ming; LONG Zuxi; WANG Yongwei; PAN Yuxuan; WANG Jun (浙江大学学报. 农业与生命科学版)
To investigate the impact of soil physical properties and driving velocity on the driving performance of a tracked tractor and obtain better operating conditions on paddy soils in the plastic state, a paddy soil mechanical model and a tracked tractor physical model were established using the RecurDyn, a multi-body dynamics software. The method of the quadratic orthogonal rotating combination design of four factors and five levels was applied to determine the impacts of clay content, moisture content, density of soils and driving velocity on the driving resistance and subsidence depth. The modeling results indicated that the driving resistance was positively associated with clay content and moisture content of soils, but negatively associated with soil density and driving velocity. The contribution rates of the factors to the driving resistance from high to low followed the order as soil moisture content, driving velocity, soil density, and soil density combined with soil clay content. The subsidence depth increased with greater soil moisture content but decreased with higher soil clay content, soil density, and driving velocity. The contribution rates of the variables to subsidence depth were ordered as soil moisture content, soil density, soil clay content, clay content combined with moisture content, clay content combined with driving velocity, and moisture content combined with driving velocity. Overall, this study quantifies the relationships among soil clay content, soil moisture content, soil density, driving velocity and driving resistance, subsidence depth of a tracked tractor using the modeling approach; and according to the soil clay content and density, the model can be used to optimize the soil moisture content and driving velocity when the driving resistance is minimum.